Terveyden lukutaidon yhteys ikääntyneen henkilön elämänlaatuun ja elämänlaadun muutokseen ajassa - Niemelä, Veera (2025)
As the population ages, maintaining a sufficient quality of life becomes an important public health goal so that the later years of life retain their dignity. Regarding quality of life, a sense of meaning, maintaining social relationships, and experiencing well-being regardless of one’s objective state of health are essential. Health literacy refers to an individual’s ability to find, understand, appraise, and apply health information. Sufficient health literacy enables independent health-related decision-making, whereas insufficient health literacy weakens autonomy and limits independence, freedom, and self-worth. The association between health literacy and quality of life has not been studied in the older community-dwelling Finnish population. This master’s thesis examines whether health literacy is associated with quality of life and changes in quality of life over a four-year follow-up period.